2022
DOI: 10.1139/apnm-2021-0438
|View full text |Cite|
|
Sign up to set email alerts
|

Leisure sedentary time and physical activity are higher in neighbourhoods with denser greenness and better built environments: an analysis of the Canadian Longitudinal Study on Aging

Abstract: Associations of environmental variables with physical activity and sedentary time using data from the Canadian Longitudinal Study on Aging, and the Canadian Urban Environment Research Consortium (Canadian Active Living Environments (Can-ALE) dataset, and Normalized Difference Vegetation Index (NDVI, greenness) dataset) were assessed. The main outcome variables were physical activity and sedentary time as measured by a modified version of the Physical Activity for Elderly Scale. The sample consisted of adults a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…Previous studies often suggested that participants with more neighborhood greenspace were at lower or equal risk of higher waist-hip ratio and obesity ( Luo et al, 2020 ),( Nichani et al, 2020 ),( O'Callaghan-Gordo et al, 2020 ). Moreover, the existing evidence for association between greenspace and sedentary time was inconsistent: a study in Brazil showed that no association between screen time and greenspace was found ( Parajára et al, 2021 ); a study in Mexico found that greater time in greenspace was associated with decreased sedentary time ( Benjamin-Neelon et al, 2019 ); and another study in Canada found that middle-aged and older adults with more greenspace reported more leisure sedentary time ( Klicnik et al, 2022 ). Here we found that in the U.K., although greenspace could benefit overall health, more greenspace was associated with longer sedentary time and higher risk of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies often suggested that participants with more neighborhood greenspace were at lower or equal risk of higher waist-hip ratio and obesity ( Luo et al, 2020 ),( Nichani et al, 2020 ),( O'Callaghan-Gordo et al, 2020 ). Moreover, the existing evidence for association between greenspace and sedentary time was inconsistent: a study in Brazil showed that no association between screen time and greenspace was found ( Parajára et al, 2021 ); a study in Mexico found that greater time in greenspace was associated with decreased sedentary time ( Benjamin-Neelon et al, 2019 ); and another study in Canada found that middle-aged and older adults with more greenspace reported more leisure sedentary time ( Klicnik et al, 2022 ). Here we found that in the U.K., although greenspace could benefit overall health, more greenspace was associated with longer sedentary time and higher risk of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…One early study has suggested that greater urban greenness is associated with superior mental health in the first wave of the CLSA (Abraham Cottagiri et al, 2022). Future research trends in this area will likely: consider additional aspects of the environment as a contributor to mental health; evaluate whether there are longitudinal associations; and identify potential mechanisms that link the environment to mental health, such as behaviours (Klicnik et al, 2022), social connections (Gan et al, 2022), and disease (Grant et al, 2021).…”
Section: Environmental Influences On Mental Healthmentioning
confidence: 99%
“…As such, for participants with data collected in 2012 (n = 3,802), the average of 2011 and 2013 NDVI data were used because NDVI values for 2011 and 2013 were significantly different (ts = 8.46 -37.85; ps < .001). This approach is consistent with recent research practices (e.g., Klicnik et al, 2022). Measures of NDVI included: annual mean, growing season mean, and annual maximum values matched to participant postal codes and at 250-, 500-, and 1000-meter buffers from participant postal codes (Browning & Lee, 2017;The Canadian Urban Environmental Health Research Consortium, 2022b, 2022a, 2022c.…”
Section: Green Spacementioning
confidence: 92%
“…Green space data were provided by CANUE and included 19 measures of the Normalized Difference Vegetation Index (NDVI;CanMap Postal Code Suite, 2015;Gorelick et al, 2017;United States Geological Survey (USGS), 1984b, 1984a, 2013b, 2013a. NDVI is a commonly used measure of ground level green space in epidemiological and health behaviour research (e.g., Crouse et al, 2021;Klicnik et al, 2022;Villeneuve et al, 2012). NDVI provides an estimate of vegetation within specified radii using a mathematical comparison of absorbed visible red light and reflected near-infrared light to produce a value ranging from -1 to 1.…”
Section: Green Spacementioning
confidence: 99%
See 1 more Smart Citation